Increasing Commitment through the Effect of Green Training and Development and Green Behavior in State-Owned Bank Employees - Sylvia Diana Purba; Hilarius Deonaldy Wiranatha; Endang Sulistyaningsih (Binus Business Review, 2024)
The rising concern of global warming has spurred numerous organizations and companies worldwide to adopt green business strategies, which integrate environmental management with Human Resource Management (HRM), notably through implementing Green HRM (GHRM). The Indonesian government has also promoted eco-green applications in support of environmental sustainability in various government institutions, including state-owned banks, as a pioneer in the GHRM program. The research evaluated the influence of green training and development on organizational commitment among employees at a state-owned bank. The research raised the novelty by modifying indicators that were relevant to banking activity. Additionally, it examined the role of green behavior as a mediating factor in the relationship between green training and organizational commitment. The research involved 200 employees from the head office of a state-owned bank, using non-probability and convenience sampling methods. Then, data were analyzed using Structural Equation Modeling (SEM) and the Smart PLS 3.0 software. The findings indicate that green training and development significantly influence green behavior, substantially enhancing organizational commitment. A shift towards a more environmentally conscious work culture strengthens employees’ commitment. The management of the state-owned bank, particularly the HRM departments, is advised to focus on enhancing and implementing GHRM practices. The practices include integrating green training and development into their in-person and online programs to promote green behavior and positively impact employee organizational commitment. The research underscores the mediating role of green behavior in the relationship between green training and organizational commitment, although the direct effects are more pronounced than indirect ones.